DEPIGMENTING AGENT MELANOTOKSIK PADA PENGOBATAN MELASMA - Winawati Eka Putri; Yuli Kurniawati; Tantawi Djauhari (Jurnal Ilmu Kesehatan dan Kesehatan, 2018)
Abstract: Human skin color is determined by melanin pigment,either eumelanin or feomelanin.Melanogenesis is a melanin synthesized process that is initiated with tirosin oxidation to DOPAquinoneby tirosinase, and then auto-oxidation to DOPA and DOPAchrome. Eumelanin are formed fromDOPAchrome, while pheomelanin from DOPAquinone with the presence of cysteine or gluthathione.Hyperpigmentation disorders like melasma, are difficult to treat especially in dark skinned individuals.Treatment of melasma can be topical or physical. Topical agent can use depigmenting agent, eitherindividual or combination with other. Depigmenting agent can be melanotoxic or toxic to melanocytewhich can be cell killing or cell damage. Hydroquinone, monomethyl of hydroqunone, N-acetyl-4-Scysteaminylphenol ,and azelaic acid are depigmenting agents melanotoxic. Majority of those agents actas tirosinase inhibitors which cause deactivation of tirosinase. The use of those agents in combinationare better to minimalize side effect of agents.